A Practical Approach for Software Engineering Teaching: A Case Study for Real Time System Development - Campos, Henrique Fernandes de; Romano, Breno Lisi; Braga e Silva, Gláucia; Vieira, Ricardo Godoi; Cunha, Adilson Marques da (Anais do Workshop sobre Educação em Computação (WEI), 2009)
This paper reports an academic experience at the Instituto Tecnológico de Aeronáutica ITA in real time embedded system development. The adopted methodology involves tailoring of the IBM Rational Unified Process (RUP) supported by Software Engineering recommended practices. A case study related to a hydrometeorological context is used to demonstrate the application of this methodology together with the main artifacts produced during some development process activities.